Adat and Islamic Law in Contemporary Aceh, Indonesia: Unequal Coexistence and Asymmetric Contestation - Salim, Arskal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Discussions on adat and Islamic law in Muslim societies have been focusing on a tension between the two entities. By looking at adat and Islamic law being respectively applied in contemporary Aceh, this article offers a different approach by considering the unbalanced relationship between adat and Islamic law and thus argues that both have been unequally coexisting and asymmetrically contesting with one another. Based on a lengthy ethnographic fieldwork and recurring visits to Aceh, this study discusses the ways in which adat of Aceh has been reinvigorated along with the official implementation of Islamic law in the past two decades. It includes efforts: 1) to establish adat bureaucracy, 2) to restore a cultural sovereignty of adat, 3) to retrieve adat rights to natural resources, and 4) to reinforce adat mechanism of dispute settlement. Despite all these efforts, however, adat appears to be subordinate and secondary.